Development and validation of HPLC-DAD methods for the analysis of two novel iron chelators with potent anti-cancer activity - Mrkvičková, Zlata; Štěrbová-Kovaříková, Petra; Klimeš, Jiří; Kalinowski, Danuta; Richardson, Des R (Journal of pharmaceutical and biomedical analysis, 2007)
Di-2-pyridylketone isonicotinoyl hydrazone (PKIH) and di-2-pyridylketone-4,4-dimethyl-3-thiosemicarbazone (Dp44mT) novel iron chelators which possess marked anti-cancer activity in vivo. However, further progress in the development of these drug candidates requires precise and convenient methods for their qualitative and quantitative analysis. The aim of this study was to develop and validate HPLC methods suitable for the purity and stability evaluation of Dp44mT and PKIH and subsequently to employ these methods in stress tests addressing their chemical stability. The chromatographic analyses of both chelators were accomplished via HPLC using a Discovery HSF5 column (25 cm x 4 mm; 5 microm). For separation of Dp44mT and its synthetic precursors, the mobile phase was composed of a mixture of 2 mM EDTA and acetonitrile in a ratio 60:40 (v/v). A desirable separation of PKIH from its synthetic precursors was achieved with a mixture of 0.01 M phosphate buffer (pH 3.0), methanol and acetonitrile in a ratio of 65:21:14 (v/v/v) with the addition of EDTA (2 mM). In order to confirm the utility of these HPLC methods for measuring these drugs and their stability, Dp44mT and PKIH were subjected to chemical stress tests. These experiments showed that Dp44mT was relatively stable against hydrolytic degradation, but quite sensitive to oxidation. On the other hand, PKIH was slightly sensitive to acid-catalyzed hydrolysis, but it was relatively stable under other tested conditions. Furthermore, these studies confirmed the utility of these methods not only for appropriate evaluation of purity but also stability. The analytical methods developed and validated in this study, as well as the basic data on the chemical stability, should further support the development of both these novel anti-cancer chelators as promising drug candidates.
Keywords: Antineoplastic Agents; Reproducibility of Results; Chromatography, High Pressure Liquid; koncentrace vodíkových iontů; Financing, Organized; Chelating Agents; Iron Chelating Agents; chelátory železa; chelátory; Hydrogen-Ion Concentration; protinádorové látky; financování organizované; stabilita léku; Drug Stability; reprodukovatelnost výsledků; vysokoúčinná kapalinová chromatografie